HUBUNGAN KEBIASAAN KONSUMSI SPAGHETTI INSTAN DENGAN PRODUKTIVITAS DAN KINERJA AKADEMIK MAHASISWA - Alika Dindania Sahari; Dian Sudiantini, Edo Putra Edina, Hanifah Nur Azizah, Nafisa Salsabilla, Ulya Rahman Maulana (ADISAM PUBLISHER, 2024)
This research aims to determine the relationship between instant spaghetti consumption habits and student productivity and academic performance. The research method used was a survey of 40 students. The research results show that there is a relationship between the habit of consuming instant spaghetti and students' academic productivity, but there is no relationship with students' academic performance. Students who often consume instant spaghetti have lower productivity than students who rarely consume instant spaghetti.